Экологическая геология: проблема глобальных катастроф - Соловьёв, В.О.; Soloviev, V.O. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2009)
На примере рассмотрения глобальных природных катастроф в течение истории развития человека показаны возможности данного направления экологической геологии – расшифровывать условия формирования общества в зависимости от процессов внешней среды, решать определенные вопросы палеоэкологии и археологии, делать возможные прогнозы в этой области. On an instance of consideration of global natural catastrophes during history of evolution of the person opportunities of the produced direction of ecological geology are demonstrated - to decode conditions of forming of a society depending on processes of an environment, to solve the determined questions paleoecology and archeology, to do possible forecasts in this field.
Ecological geology: the problem of global catastrophes
Keywords: global natural disaster; external environment; paleoecology; archeology; глобальные природные катастрофы; внешняя среда; палеоэкология; археология